PENGARUH FAKTOR PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PELAYANAN DI INSTALASI RAWAT INAP RSUD HAJI MAKASSAR - Andi Khairul Musyawir Khairul; Muhammad Saputra (Public Health And Medicine Journal, 2024)
Background. The decision-making process for purchasing healthcare services involves a complex evaluation of available alternatives, influenced by factors such as perception, attitudes, and social, cultural, personal, and psychological factors. This study aims to identify and analyze the impact of consumer behavior factors on the purchase decisions for inpatient services at RSUD Haji Makassar. Consequently, this research is expected to provide valuable insights for the hospital to improve service quality and marketing strategies to retain and attract consumer interest. Method. This study employs a quantitative approach with a survey design to collect data from respondents who are general patients that have used inpatient services at RSUD Haji Makassar. The sample consists of 88 respondents, and data analysis is conducted using chi- square analysis. Results. The findings indicate a significant influence of cultural factors on purchase decisions at the Inpatient Installation of RSUD Haji Makassar. There is also a significant effect of social factors on purchase decisions. Personal factors have a significant impact on purchase decisions, and psychological factors significantly influence purchase decisions at RSUD Haji Makassar. Conclusion. Cultural, social, personal, and psychological factors all significantly affect the purchase decisions for healthcare services at the inpatient installation of RSUD Haji Makassar. Recommendation: Develop services tailored to individual patient needs and preferences, including flexible care options. Address patient concerns, maintain high healthcare service standards, and build consumer trust by consistently providing excellent service.